Dirty versus clean firms' relocation under international trade and imperfect competition - Julie Ing; Jean-Philippe Nicolai (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
This paper develops a simple partial equilibrium model with two countries (North and South) to fathom the effects of firms' relocation in a context of international and imperfect competition. Two different production technologies are considered, a clean technology and a dirty one, and the effects of relocation according to the kind of technology used by the relocated firms are determined. Two heterogeneous firms in the North and only one dirty firm in the South are assumed and the four different possible scenarios are compared: neither firm relocates, the two northern firms relocate, the clean one relocates and the dirty one relocates. This paper demonstrates that the relocation of a dirty firm as compared to the relocation of a clean firm is worse for the environment, better for northern consumers, and better for the domestic profits. Moreover, the relocation of a dirty firm always increases global emissions, while the relocation of a clean firm may decrease global emissions.
Keywords: L13; Q53; Q58; 330; Relocation; Emissions tax; Trade of polluting goods; Dirty and clean production technologies; Imperfect competition